Comprehensive analysis of a single-story single-bay RC frame with varied reinforcement detailing - Al-Sayegh, Ammar T. (Frontiers in Built Environment, 2025)
This study examines various reinforcement detailing approaches in Single-Story-Single-Bay (SSSB) reinforced concrete (RC) frames using the design tool SAP 2000 and nonlinear finite element analysis (NLFEA) with ABAQUS. A finite element model of the SSSB was developed in ABAQUS, adjusted based on experimental data from prior tests. The Concrete Damaged Plasticity (CDP) model simulated the behavior of concrete, while steel reinforcement bars were modelled as bilinear elastoplastic materials. After calibration, the peak lateral load and displacement values from the FEA models closely matched experimental results. The Control Model (CM) served as a basis for new models: (i) Half Diameter of Stirrups in the Beam (HDB), (ii) Half Diameter of Stirrups in both Beam and Columns (HDBC), and (iii) Double Spacing of Stirrups in Beam and Columns (DSBC). This analysis evaluated the effect of key design parameters, specifically the transverse reinforcement ratio (ρt), on SSSB’s load-carrying capacity. Results showed HDB had a 10.2% increase in lateral load compared to CM, while HDBC and DSBC demonstrated decreases of 15.8% and 15.5%, respectively, relative to experimental values.